With a Little Help from my Enteric Microbial Friends - Berkhout, Ben (Frontiers in Medicine, 2015)
Although the disciplines of bacteriology and virology frequently come together in the setting of a diagnostic medical microbiology laboratory, the two scientific fields are usually miles apart. The microbiologists basically form two non-overlapping groups of scientists, the bacteriologists and virologists, that go to separate meetings and that do not easily intermingle. Some recent research findings about elegant virus-bacterium interactions may change this situation. Obviously, interactions between these two microbes can occur only when they co-localize, which most likely occurs in the gut/intestines where 1014 commensal bacteria reside (the microbiota). We review findings on the following enteric microbial tandems: norovirus- Enterobacter cloacae, mouse mammary tumor virus (MMTV) – bacterial lipopolysaccharide (LPS), poliovirus and reovirus – intestinal bacteria. The close bacterium-virus interplay may also present options to develop unique therapeutic strategies for those infected and to prevent further virus spread and thus minimize the risk for the community.